2021
DOI: 10.1039/d0tc04547k
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient thermally activated delayed fluorescence emitters enabled by double charge transfer pathways via ortho-linked triarylboron/carbazole hybrids

Abstract: Two thermally activated delayed fluorescence emitters with double charge transfer pathways have been studied. Owing to the restricted ortho-linked D–A–D configuration, both emitters exhibited excellent luminescent performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Among these emitters, T‐CNDF‐T‐ t Cz ( 64 ) exhibited sky‐blue emission and gave an EQE of up to 21.0 % in non‐doped OLED devices. Later in 2021, the group of Yang [45] introduced two carbazoles and tert‐butyl carbazole ( t Cz) units on the ortho ‐position of triarylboron. The molecules exhibited a typical D–A–D structure and the highly distorted molecular structure greatly suppressed non‐radiative transitions and improved the PLQYs.…”
Section: Ortho‐linked D–a Type Tadf Emittersmentioning
confidence: 99%
“…Among these emitters, T‐CNDF‐T‐ t Cz ( 64 ) exhibited sky‐blue emission and gave an EQE of up to 21.0 % in non‐doped OLED devices. Later in 2021, the group of Yang [45] introduced two carbazoles and tert‐butyl carbazole ( t Cz) units on the ortho ‐position of triarylboron. The molecules exhibited a typical D–A–D structure and the highly distorted molecular structure greatly suppressed non‐radiative transitions and improved the PLQYs.…”
Section: Ortho‐linked D–a Type Tadf Emittersmentioning
confidence: 99%
“…Then phenol or 4-(tert-butyl)phenol were subjected to Ullmann coupling to give the precursor 3 and 5, respectively. The target materials 3TBO and 5TBO were synthesized in one-pot borylation and confirmed by 1 H NMR and 13 C NMR spectroscopy, as well as mass spectrometry. 3TBO and 5TBO show good solubility in common organic solvents with the introduction of tert-butyl solubilizing group.…”
Section: Molecular Synthesismentioning
confidence: 99%
“…To date, numerous D/A systems have been investigated [10][11][12][13][14]. As the donors are mainly aryl amines [15,16], the innovations of the building blocks are mostly concentrated on acceptors [14].…”
Section: Introductionmentioning
confidence: 99%
“…7 Yang's group found that OLEDs using o B-2Cz and o B-2tCz as emissive guests can reach their maximum EQEs of 28.1% and 27.5%, respectively. 8 Li et al synthesized three molecules 3Cz-Ph-CN, 3Cz-mPh-CN and 3Ph-Cz-CN, which achieved high external quantum efficiency of 18.1%. 9 Duan et al obtained a high reverse intersystem crossing rate ( K RISC ) of 2.36 × 10 6 s −1 with an emission peak of 456 nm and maximum EQE of 22.8% by replacing the stronger cyano acceptor with the weak acceptor of cyanophenyl.…”
Section: Introductionmentioning
confidence: 99%